Indices of precipitation extremes in Southern Portugal-a geostatistical approach - Dur̃ao, R. (2019)
Dur̃ao, R., J.Pereira, M., C.Costa, A., M.Ĉorte-Real, J., & Soares, A. (2009). Indices of precipitation extremes in Southern Portugal-a geostatistical approach. Natural Hazards and Earth System Science, 9(1), 241-250. https://doi.org/10.5194/nhess-9-241-2009